2018
DOI: 10.1007/s11079-018-9518-8
|View full text |Cite
|
Sign up to set email alerts
|

Global Value Chains and Wages: Multi-Country Evidence from Linked Worker-Industry Data

Abstract: This paper uses a multi-country microeconomic setting to contribute to the literature on the nexus between production fragmentation and wages. Exploiting a rich dataset on over 110,000 workers from nine Eastern and Western European countries and the United States, we study the relationship between individual workers' wages and industry ties into global value chains (GVCs). We find an inverse (but weak) relationship between the degree of industries' involvement in GVCs and wages. Workers employed in routine occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 91 publications
(117 reference statements)
3
12
0
Order By: Relevance
“…To our knowledge, current research on these concepts using LIS data operationalize them in much cruder ways on limited samples (e.g. Mueller et al, 2015;Parteka and Wolszczak-Derlacz, 2016). Both RTI and OFFS are correlated with work hours and labor incomes in ways that are consistent with existing theory.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To our knowledge, current research on these concepts using LIS data operationalize them in much cruder ways on limited samples (e.g. Mueller et al, 2015;Parteka and Wolszczak-Derlacz, 2016). Both RTI and OFFS are correlated with work hours and labor incomes in ways that are consistent with existing theory.…”
Section: Discussionsupporting
confidence: 62%
“…To our knowledge, current research on these concepts using LIS data operationalize them in much cruder ways on limited samples (e.g. Mueller et al, 2015; Parteka and Wolszczak-Derlacz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Growing industrial interdependence across countries due to the offshoring of production appears to have come at a cost to workers in Europe and the United States, especially those who perform more routine tasks, who tend to be less well educated. However, here too, the effects that have been identified empirically appear to be quite modest (Parteka and Wolszczak-Derlacz 2016).…”
Section: Inequality Within Countriesmentioning
confidence: 73%
“…Similarly, Szymczak et al (2019) use the CEECs sample to show how the position of industries in the production chain affects wages. Parteka and Wolszczak-Derlacz (2019), constructing a cross-sectional dataset on nine European countries and the United States, is the work most resembling the present paper in terms of data and methodology. Those results suggested that growing cross-border industrial interdependence (measured as the foreign share in the industry's value added) decreases the wages of some workers, namely those who perform more routine tasks and are less well educated.…”
Section: Production Fragmentation Gvc and Wages In Europe-the Empirical Evidencementioning
confidence: 99%